Mathematics in seltok: a Banyuwangi traditional game - Novita Purnamasari Supahmi; Rachmaniah Mirza Hariastuti; Widie Nurmahmudy (Journal of Science and Education (JSE), 2022)
Seltok is one of the traditional games of the Banyuwangi community in East Java. This game is attempted to be preserved by the “Kampoeng Batara”, a traditional game community located in the Papring, Kalipuro District, Banyuwangi. It is important to preserve traditional games, one of which is because the games contain learning concepts, such as mathematics. Unfortunately, these mathematical concepts have not been fully identified. The exploration of the seltok game in Kampoeng Batara aims to identify the mathematical concepts in the game. The research informants were one manager and two members of Kampoeng Batara community. Data collection was carried out by participatory observation, in-depth interviews, and cultural documentation. The data obtained were analyzed qualitatively. The identification results show the existence of mathematical concepts: measurement with non-standard units, geometry (circle and tube), set, relation, combination, and probability in the seltok game.